Lectotypification of the name Premna wightiana Schauer (Lamiaceae) and notes on its distribution in India - Kumar, Vannaratta Veettil Naveen; Prabhukumar, Konickal Mambetta; Cheriyath, Mohammed Shameer; Jagadeesan, Raveendran; Sunil, Chandrasseril Narayanan; Balachandran, Indira (Phytotaxa, 2023)
N/A